Space-Charge-Limited Dark Injection (SCL DI) transient measurements - Yap B.K.; Koh S.P.; Tiong S.K.; Ong C.N. (2023)
It is not an easy task to probe the mobility of nanoscale thin layers without using expensive and sophisticated equipments such as Time-of-flight photocurrent charge carrier mobility measurement. We present here a powerful yet cost-effective technique, namely the Space-Charge-Limited Dark Injection (SCL DI) Transient Measurement that allows us to confirm an ohmic injecting interface, to determine the mobility values of the bulk materials and to study the injection efficiency of the interfaces of the semiconductor materials. 2010 IEEE.